Fortification of Bioadhesive with Phenol Formaldehyde: Caracteristics and its Application for Afrika Laminated Wood - Dini Lestari; Rima Vera Ningsih; Fauzan Fahrussiam; Sofia Mustamu (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Nowadays, there is growing interested in development of environmentally friendly and nontoxic wood adhesives. The objective of this research was to determined the characteristics of starch, tannin, and cowhide adhesives by adding phenol formaldehyde as a fortifier. The quality of its bonding properties for afrika laminated wood was also investigated. Determination of characterization of bioadhesive was conducted based on SNI 06-4567-1998. The quality of bonding properties for laminated wood was conducted based on SNI 06-6049-1991 and all parameters values compare to JAS 1152-2007. Based on the research characteristic of bioadhesive values for visualization tes, viscosity tes fullfill SNI 06-4567-1998 requirement. For pH, solid content, and glatination time not all sampel fullfill requirement values. All parameters of physical properties of all of sample afrika laminated wood meet the JSA 1152-2007 requirement. For Afrika laminated wood made from starch and tannin adhesive have good value for delamination test. Moreover, for shear strength parameter test not fullfill JSA 1152-2007 requirement. All of sampel have only for interior purposes.